Forms of Otherness: an epistemilogical and political challenge (Andamios, Revista de Investigación Social, 2011)
How do we know and think about the radical and irreducible difference to the “same”? And how we relate to it? Western thought has answered both questions: with ontology, the first, with ethics and politics the second. This essay shows the operation of both strategies through various stages of thinking (ontology, language, politics) to show what forms of otherness works and are worked by the philosophy that we recognize. On the final I insist on re-politicizing the thought of difference from the perspective of radical democracy in times of globalization.
Keywords: difference; the other; the same; exclusion; language